Measurement of the production cross section of prompt j/psi mesons in association with a W (+/-) boson in pp collisions root s=7 TeV with the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; et al. (2014)
The process pp → W±J/ψ provides a powerful probe of the production mechanism of charmonium in hadronic collisions, and is also sensitive to multiple parton interactions in the colliding protons. Using the 2011 ATLAS dataset of 4.5 fb-1 of p s = 7TeV pp collisions at the LHC, the first observation is made of the production of W± + prompt J/ events in hadronic collisions, using W± → μ and J/ψ → μ+μ-. A yield of 27.4±7.5 -6.5 W± + prompt J/ψ events is observed, with a statistical significance of 5.1. The production rate as a ratio to the inclusive W± boson production rate is measured, and the double parton scattering contribution to the cross section is estimated. Copyright CERN, for the benefit of the ATLAS Collaboration.